Effectiveness of green strategies to reduce carbon emission in the Putrajaya Campus Buildings of Universiti Tenaga Nasional - Ba-Batin A.S.S.; Haider H.A.A.; Wong L.S.; Taresh H.A.A. (Science Publishing Corporation Inc, 2023)
Low Carbon Buildings are regarded as structures with low carbon emission in the construction sector. They are environment-friendly in a sense that they contribute to the reduction in carbon emission through optimization of their energy consumption and passive cooling system. This study concentrated on green strategies that can reduce carbon emission of Putrajaya Campus buildings of Universiti Tenaga Nasional (UNITEN). Survey method in the form of questionnaire was applied to gather sufficient data for the research work. The survey work was performed on UNITEN building occupiers with diverse background inclusive of students, academic and non-academic staffs. The primary result implies that the methods of insulating the wall and utilization of energy saving air conditioners are most effective at reducing carbon emission of the buildings. It was also found that there is a low correlation with R-square value of 0.017 between the awareness on the impact of carbon emission from the air conditioning buildings and the awareness on climate change issue. This implies that there is a need for active measures to be taken to educate the respondents on the importance to reduce carbon emission of buildings in order to slow down climate change. 2018 Authors.